PERFORMANCE ANALYSIS OF PAPR REDUCTION IN OICF TECHNIQUES WITH OFDM SYSTEM (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
The Iterative Clipping and Filtering (ICF) has been a well-known technique to reduce the peak to average power ratio (PAPR) in orthogonal frequency division multiplexing (OFDM) signals. Orthogonal Frequency Division Multiplexing (OFDM) has become the popular modulation technique in high speed wireless communications. It has been more advantageous over other technologies. This Proposed technique shows better performance for reduction of PAPR in any technique that can be used according to performance. In this paper Simulation results show that after iterations, the original OICF algorithm can achieve the desired PAPR while the simplified one exhibits the performance for a 64, 128, 256 and 512-subcarrier and Quadrature phase shift keying (QPSK) in modulated OFDM system, the PAPR-reduction performance have been draw in CCDF versus PAPR (dB) by Matlab R2013a toll.